Visible and ultraviolet antibacterial behavior in PVDF–TiO2 nanocomposite films. (October 2015) - Muñoz-Bonilla, A.; Kubacka, A.; Fernández-García, M.; Ferrer, M.; Fernández-García, M.; Cerrada, M.L.
Graphical abstract: Highlights: PVDF–TiO2 nanocomposites are highly efficient biocidal materials under UV light. These hybrids surprisingly maintain antimicrobial features within visible range. Appropriate interfacial interactions lead to an increase of the absorption at visible region. Anatase incorporation does not alter the PVDF crystalline lattice developed. Some crystalline characteristics are dependent on TiO2 content. Abstract: Highly efficient antibacterial nanocomposite films consisting of a commercially available poly(vinylidene difluoride) (PVDF) incorporating synthesized TiO2 nanoparticles have been prepared with different anatase contents by a simple approach with absence of any solvent. These materials display powerful antimicrobial activity toward both Gram-negative and Gram-positive bacteria under UV and, surprisingly, visible lights. Their optical characterization has pointed out that absorption is significantly increased in the nanocomposites at the visible range, being this aspect behind the excellent capability exhibited against microorganisms.